2001
DOI: 10.1352/0895-8017(2001)106<0401:qacosl>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Costs of Supported Living Residences and Group Homes in the United Kingdom

Abstract: Information was collected on 63 adults in supported living residences, 55 adults in small group homes, and 152 adults in large group homes. Results indicated that (a) there were no statistically significant differences in service costs once these had been adjusted to take account of participant characteristics; (b) compared with participants living in small group homes, those in supported living residences had greater choice, participated in more community-based activities, experienced fewer scheduled activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
82
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(94 citation statements)
references
References 28 publications
11
82
1
Order By: Relevance
“…The criteria for inclusion were people aged 18 years or over, self-identification as a person with intellectual disability, in receipt of a disability service funded by the Department of Human Services, and a supported living arrangement (i.e., living alone, or with no more than two other people who were not parents or siblings, where housing and support were separated). This latter inclusion criterion was based on Kinsella's (1993) conceptualisation of supported living, as separating housing and support, and Emerson et al's (2001) definition as being a household of three or fewer people.…”
Section: Recruitment and Description Of Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The criteria for inclusion were people aged 18 years or over, self-identification as a person with intellectual disability, in receipt of a disability service funded by the Department of Human Services, and a supported living arrangement (i.e., living alone, or with no more than two other people who were not parents or siblings, where housing and support were separated). This latter inclusion criterion was based on Kinsella's (1993) conceptualisation of supported living, as separating housing and support, and Emerson et al's (2001) definition as being a household of three or fewer people.…”
Section: Recruitment and Description Of Participantsmentioning
confidence: 99%
“…Few studies have systematically investigated the characteristics of communities, or formal and informal support arrangements associated with better outcomes in supported living. Locality is suggested as important by Emerson et al (2001). Stainton et al (2011) speculated about the importance of having informal support from family, and a recent Australian study identified the importance of family support in moving to supported living .…”
Section: Introductionmentioning
confidence: 99%
“…For example, in the US it is known as semi-independent living and refers to 1-4 people living together with dropin paid support from a disability support agency that does not extend to 24-hour support (Stancliffe & Keane, 2000), whereas in England, it can include provision of 24-hour support (Mansell, 2010). Supported living models are increasingly becoming an option in the US (Larson, Salmi, Smith, Anderson, & Hewitt, 2013), UK (Emerson et al, 2001;McConkey, Keogh, Bunting, Garcia Iriarte, & Watson, 2016;Perry, Firth, Puppa, Wilson, & Felce, 2012), and Australia (Stancliffe, 2002). The progressive introduction of individualised funding mechanisms in all Australian states through the National Disability Insurance Scheme (NDIS) between 2016-2019 is widely expected to increase availability of supported living for existing service users in group homes and people on accommodation waiting lists (Productivity Commission, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Research in the UK and US comparing supported living to group homes and controlling for individual differences of service users found it to be advantageous on quality of life domains of choice and some aspects of social inclusion (most often frequency and variety of community activities), as well as being significantly more cost effective (Emerson et al, 2001;F e l c ee ta l . ,2008;H o w e ,H o r n e r ,&N e w t o n , 1998; Perry et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation